ERGONOMI BEBAN KERJA FISIK PEKERJA BAGIAN PRODUKSI BERBASIS METODE REBA - HANAFIE, AHMAD; Syarifuddin, Rizal; Syafrillah, Syafrillah (LPPM-ITEBA, 2023)
Work-related disorders (musculoskeletal disorders/MSDs) are one of the most important health problems faced by ergonomics. Musculoskeletal Disorders (MSDs) are the most common health-related diseases used today, the purpose of this study was to evaluate the ergonomics of the workload of physical workers in the production department based on the Reba method. The research method in research using descriptive method. The object of this research focuses on workers in the production sector. The results of the analysis show that evaluating the workload of workers when carrying out the chair production process results for all activities have a risk level of 7 with a moderate risk category. Activities that have a risk level of 7 with a moderate risk category require inspection and change. From the results of the evaluation, the proposed improvements that need to be made are by adding ergonomic work facilities and recommendations for safe work postures for workers.